Kebijakan Publik Yang Berbasis Hak Asasi Manusia - Joko Sriwidodo; Dwi Andayani Budisetyowati; Palmawati Taher (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Public policy is an instrument for resolving conflicts in society. Public policies based on human rights are public policies that are formed to become a reference in providing services to the community by prioritizing human values. The formation of public policies based on human rights itself is in accordance with the mandate of Pancasila, the 1945 Constitution of the Republic of Indonesia, and Law Number 39 of 1999 concerning Human Rights itself. This research aims to contribute knowledge to policy makers in implementing human rights-based public policies. This research is research using library research. Public policy is a series of policy decisions made by a person or group of people in realizing the goals of every problem experienced by society. Public policy based on human rights in Indonesia is a relatively new policy. This human rights-based public policy has only been implemented within the Ministry of Law and Human Rights with the issuance of Minister of Law and Human Rights Regulation Number 27 of 2018 concerning Human Rights-Based Public Service Awards, which was then refined by replacing this regulation with Minister of Law and Human Rights Regulation (Permenkumham) Number 2 of 2022 concerning Human Rights-Based Public Services (P2HAM). The issuance of the Permenkumham P2HAM is in accordance with the public service standards regulated in Law Number 25 of 2009 concerning Public Services. In order to produce good and equitable human rights-based public services, it is necessary to have human rights-based public policies that apply broadly and evenly. Thus, it is necessary to make human rights-based public policy rules in all sectors, so that injustice does not occur.